2017
DOI: 10.1063/1.4973720
|View full text |Cite
|
Sign up to set email alerts
|

Tunable microbubble generator using electrolysis and ultrasound

Abstract: International audienceThis letter reports on a method for producing on demand calibrated bubbles in a non-chemically controlled solution using localized micro-electrolysis and ultrasound. Implementing a feedback loop in the process leads to a point source of stable mono-dispersed microbubbles. This approach overcomes the inertial constraints encountered in microfluidics with the possibility to produce from a single to an array of calibrated bubbles. Moreover, this method avoids the use of additional surfactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…In general, water electrolysis consists of metal electrodes at anode and cathode terminal, solution (electrolyte), and voltage, as shown in Figure 2. Platinum microelectrode with a sharp conical tip is commonly used to produce dispersed micro-nanobubbles (Hammadi et al 2013;Achaoui et al 2017), where the oxygen and hydrogen evolution reaction can be observed using a high-speed visualization camera system (Li et al 2018(Li et al , 2019.…”
Section: Micro-nanobubblesmentioning
confidence: 99%
“…In general, water electrolysis consists of metal electrodes at anode and cathode terminal, solution (electrolyte), and voltage, as shown in Figure 2. Platinum microelectrode with a sharp conical tip is commonly used to produce dispersed micro-nanobubbles (Hammadi et al 2013;Achaoui et al 2017), where the oxygen and hydrogen evolution reaction can be observed using a high-speed visualization camera system (Li et al 2018(Li et al , 2019.…”
Section: Micro-nanobubblesmentioning
confidence: 99%
“…Calibrated microbubbles were recently produced from nanoelectrolysis combined with ultrasounds using tap water (non-chemically controlled) solution. 24 In this paper, we show that calibrated microbubbles of any size can be obtained at a single site by nanoelectrolysis with a chemically controlled solution, by applying a suitable electric potential during a finite time.…”
Section: Introductionmentioning
confidence: 96%
“…As a result of these features, the use of microbubble technology has been introduced in many environmental and industrial processes such as water purifcation process [7] to improve water quality of polluted lakes and marshes [8], separation process of low-density droplets including separation oil from oily water [9], and medical therapeutic applications [7]. Several techniques can be applied to generate microbubbles, including porous membrane [10], Venturi-type [9], electrolysis and ultrasound [11], a constant fow-nozzle [12], a swirling jet fow [1], and pressurized dissolution method [13]. Among these techniques, many advantages are provided by using a microbubble generator that uses swirl fow, involving low cost and simple design with high performance to generate very small bubbles [14].…”
Section: Introductionmentioning
confidence: 99%